The influence of process route on mechanical property development in sintered commercially pure and blended elemental titanium - Qangule, Lwazi (Centre for Materials Engineering, 2016)
This work focuses on optimizing the sintering process of Ti-6Al-4V using Al-V master alloy powder to achieve a cost efficient product with acceptable mechanical properties. Reference was also made to Ti-6Al-4V products produced by Clinning (University of Cape Town 2012) using elemental Al and V instead of the master alloy addition proposed in this work. Commercially pure titanium (CP-Ti, Alfa Aesar) was used in this study as a reference, since its behavior during processing is more predictable. Relative density and the microstructural feature were studied in-depth in order to understand their impact on mechanical properties. The two starting materials were sintered under vacuum (approximately 10-5 mbar) at 1000⁰C (6hrs), 1100⁰C (2, 4, 6hrs), 1200⁰C (1, 2, 4hrs) and 1300⁰C (1, 2hrs). Relative density, microstructure analysis and mechanical property measurements characterized on the as-sintered material before specimens were hot deformed at 800⁰C to 0.69 strain and subsequently annealed at 870⁰C for 1hr. Similar measurements and analyses were conducted on the samples post deformation and annealing.